Advance Reforestation Strategies: Predicting Potential Species from Available Species in Jagoi Heritage Forest (JHF) and Mycorrhizal FungiTrichoderma-Fertilizer Combined Effects on Durio zibethinus and Artocarpus heterophyllus Growth - Julia, Nelson (Universiti Malaysia Sarawak, 2024)
Reforestation can occur by two main methods namely, natural regeneration and intervention during replanting. This study consists of two experiments. Experiment 1 predicted the potential native tree species for mixed-planting reforestation in degraded areas around Bau District using the ecological criteria using the ecological criteria i.e., natural regeneration status, importance value (IV), and standing biomass (SB). The study was carried out at Jagoi Heritage Forest (JHF), Bau, Sarawak. A total of 52 (20 m x 20 m) nested quadrats were placed systematically in primary forest (PF), old secondary forest (OSF), young secondary forest (YSF), and agroforest (AF). Shannon-Wiener diversity index results showed that YSF and AF have the highest species diversity (H’ = 4.10). Kruskal-Wallis H test showed that there is a significant difference in IV (X2[3] = 12.20, p = 0.01) and SB (X2[3] = 27.29, p <0.05) between forest types. The cross-matched between Indicator species analysis (ISA) result and natural regeneration status found that Dipterocarpus sp. and Archidendron jiringa (Jack) Nielsen have the highest indicator values (based on IV and SB) and good regeneration. Thus, Dipterocarpus sp. and A. jiringa has a higher potential for mixed-planting reforestation in degraded areas around Bau District. Meanwhile, Experiment 2 investigated the effect of mycorrhizal fungi and Trichoderma (MF-T) application with different fertilizer types and amounts on Durio zibethinus Murray (durian) and Artocarpus heterophyllus Lam. (jackfruit) growth. A randomized complete block design was used with ten replicates per species of tree per treatment. Seven treatments were used. The profile diagram shows the highest marginal mean of D. zibethinus height was at 100 g organic fertilizer (OF) with MFT (Mean = 65.52), and A. heterophyllus height was at 50 g OF with MF-T (Mean = 113.77). The marginal mean stem diameter also showed that the highest mean of D. zibethinus diameter was at 100 g chemical fertilizer (CF) with MF-T (Mean = 7.15). However, the highest marginal mean diameter for A. heterophyllus was at 50 g OF with MF-T (Mean = 8.98). The factorial ANOVA result indicated that there was a significant difference between treatments versus species of tree on height (F [6,154] = 12.44, p < 0.05) and stem diameter (F [6,154] = 5.57, p < 0.05). The Tukey post-hoc analysis showed that treatment of 50 g OF with MF-T is the most suitable treatment for the successful establishment of D. zibethinus and A. heterophyllus. The study concluded that reforestation can be achieved through two methods namely, natural regeneration and manipulation during replanting. A predictive approach based on the tree’s natural regeneration status, IV, and SB can predict successful establishment of the selected species in a new area. The replanting method with coinoculation of MF-T with OF not only helps in promoting plant growth and recovers the soil’s chemical and biological properties but also helps in reducing dependencies on chemical fertilizer.